In-situ photochemical synthesis and dielectric properties of nanocomposite thin films containing Au, Ag and MnO nanoparticles - Mutlu, Saliha; Metin, Eyup; Yuksel, Sureyya Aydin; Bayrak, Ugur; Nuhoglu, Cigdem; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Thioxanthone-Anthracene (TX-A) was used as a one-component Type II photoinitiator for the photopolymerization of PEGMEA/PEGDA monomer mixture consisting of AgNO3, HAuCl4 and MnCl2 metallic salts. In this study, we have seen that nanoparticles (NPs) are distributed differently in solution and in polymer matrices and that the particle size also changes. The size of the AuNPs (8-16 nm) synthesized in the solution in the presence of air atmosphere is smaller than the AuNPs (18-25 nm) synthesized in the polymer matrix. It is also important to state the effect of the atmosphere on the shape and size of the NPs. Thanks to the endoperoxide formation in air atmosphere, the formation of AgNPs in the range of 45-53 nm is possible in solution, while the size of AgNPs increased up to 1900 nm in nitrogen atmosphere. Additionally, radical spin densities were calculated with Density Functional Theory to understand which radical is mainly responsible for the reduction of metal ions to form metal and metal oxide nanoparticles. Peroxy radicals were found to be mainly responsible due to their much higher electron spin density compared to the other radicals. Moreover, the dielectric properties of in-situ formed AuNPs, AgNPs and MnONPs in the nanocomposite films were investigated at room temperature. For all nanocomposite films containing metal NPs, the frequency dependent dielectric constant and dielectric loss are higher than the polymeric films up to about 50 times.
Keywords: Nanocomposites; Gold nanoparticles; Silver nanoparticles; Manganese oxide; Photopolymerization; Dielectric properties; FREE-RADICAL POLYMERIZATION; THIOXANTHONE; PHOTOINITIATOR; NANOWIRES; ROUTE; Polymer Science